P259 Measures of predicting inflammatory and fibrotic strictures in Crohn's disease patients using magnetic resonance. (16th January 2018) - Stack, R; O'Brien, C; Nuzum, T; Kumar, L; Maheshwari, P; Breslin, N; Ryan, B; O'Connor, A; Murphy, I; Mc Namara, D
Abstract: Background: Small bowel (SB) Crohn's disease (CD) strictures can comprise of both inflammatory and fibrotic elements. Ideally, an accurate tool to discriminate fibrosis and inflammation would be clinically useful to guide therapy. To date no specific tool has been developed. Lesions with a dense fibrotic matrix are known to exhibit delayed gadolinium enhancement on MRI. The role of delayed enhancement in assessment of SB CD strictures is unclear. Recent evidence suggests relative contrast enhancement (REC) of >24% on delayed MRI sequences may accurately detect fibrosis. We performed a study aiming to determine the feasibility of Magnetic Resonance Enterography, MRE, SB stricture assessment with early (70s) and late (7mins) phase post gadolinium imaging. Methods: We performed a retrospective study on 208 MREs requested for patient with suspected and known Crohn's disease. Patient's disease status, demographics and biochemical markers were recorded. Patients with active inflammation or stricturing disease had imaging further assessed. All MREs were performed with additional coronal T1 sequences 7 min post gadolinium administration and were assessed by 2 independent blinded radiologist for evidence of RCE, T2 signal intensity(SI), MaRIA score and evidence of stenosis. Results: Median age 40.5 years; male n = 83(39.9%). 117, 72 and 19 patients had known CD, suspected CD and indeterminate IBD, respectively. In total, 119(57%) MREs were normal. Ileitis, strictures and fistulas were found in 40(19%), 49(24%) and 1(0.5%) patients, respectively. 69 MREs were further assessed on patients with stricturing and inflammatory ileal Crohn's disease. Median age = 42 years. Male n = 26(38%). RCE >24% and high T2 SI was recorded in 26(38%) and 35/69 (51%)respectively. MaRIA score for the cohort comprised of: Mild< 7; 5(7%), moderate 7−11; 11(16%), severe >11; 53(77%). There was no significant change in MaRIA score between 70sec and 7mins. 36(52%) had evidence of stenosis on MRE. RCE, T2SI and MaRIA score for patients with stenosis vs. no stenosis was as followed: RCE>24%; 13 v 13. High T2 SI: 30 v 5. MaRIA < 7; 2 v3. MaRIA 7–11; 6 v 5. MaRIA >11; 28 v 25. Patients with RCE< 24% and high T2SI; 23(33.3%). 20( 30.3%) patients had neither High T2SI nor RCE >24%. 12(17%) had both RCE>24% and high T2SI while 14( 20%) had RCE> 24% without high T2SI. Conclusions: Current tools such as MaRIA do not differentiate between inflammatory and stenotic disease, while T2SI may be a useful marker of stenosis. While RCE>24% was comparable in groups with both stenosis and without, further analysis is required into patients who have isolated RCE>24% and where this may be a marker of fibrotic vs. inflammatory disease.